REFORMASI BIROKRASI YANG TERINTEGRASI DALAM NEW PUBLIC SERVICE (NPS) GUNA MEWUJUDKAN PEMERINTAHAN YANG KUAT DAN BERSIH - Nanang Bagus Srihardjono; Ryka Puspitasari Restyaningrum (REFORMASI, 2017)
Abstract: Achieving a strong and clean government requires a new change of service to the community. The government should not run like a company but serve the community in a democratic, fair, equitable, non-discriminatory, honest and accountable manner. “Citizens First” should be the handle or the government's motto. The purpose of this research is to know the effort of bureaucratic reform in improving public service. This study used a qualitative approach with the determination of informants using Purposive Sampling. Data collection through interviews, observation and documentation. Data analysis techniques include: data collection, data reduction, data presentation, and drawing conclusions. The validity of data is tested through, the credibility test is by using Triangulation Technique. The result of the research proves that bureaucracy reform effort in improving public service leads to: Bureaucracy reform effort by increasing human resources (HR), bureaucracy renewal is also done in the field of management, including service procedure, absolutely done so that NPS paradigm become real in service to society with the general principles of government and provide protection and legal certainty. Keywords: Bureaucratic Reform, New Public Service.